How is the association between urinary prostate cancer antigen 3 (PCA3) levels and Gleason scores in patients suspicious of prostate cancer? - Gilani, Sasan (Int J Physiol Pathophysiol Pharmacol, 2019)
Introduction: Prostate cancer is one of the most common cancers in men which is mostly slow growing and responses well to treatments if early diagnosed. Urinary prostate cancer antigen 3 (PCA3) assay is a new method with effective results in diagnosing prostate cancer. The aim of this present study was evaluate the correlation between urinary PCA3 and Gleason scores in patients who are suspicious of prostate cancer and undergo tissue biopsies. Methods: This is a cross-sectional study which was performed in 2017-2018. The patients included this study complain of prostate problems and were selected from Nour hospital, Ali-Asghar hospital and Ordibehesht clinic in Tehran, Iran. Urinary PCA3 levels were checked in all patients and then they went under prostate biopsies. Amounts of PCA3 and Gleason scores were collected and analyzed using SPSS software. Findings: We evaluated a total number of 80 patients. 40 patients had prostate cancer and 40 had no cancer. We indicated that no significant relation was reported between Gleason scores and urinary PCA3 levels. Levels of urinary PCA3 were higher in patients with prostate cancer than in patients with no cancer (P=0.007). Discussion: Generally, urinary PCA3 test is indicated as a non-invasive method to improve the specificity of prostate cancer diagnosis and its potential predictive value was studied in numerous clinical researches, but here we found higher PCA3 levels in patients with prostate cancer than in patients with and other prostate problems. We conclude that PCA3 functions as a diagnostic test and its changes in prostate cancer need to be further studied in different populations and races.